Grain yield, nutrient balance and economics of T. Aman rice cultivation as influenced by nutrients management - Jahan, MAH S; Sarkar, MAR; Barma, NCD; Mondal, MNA; Ferdousi, MNS (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was conducted at Regional Wheat Research Centre of the Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh during 2007 and 2008. The objectives were to find out the optimum nutrient management practice for grain yield, nutrient balance and economics of T. Aman rice. Twelve nutrient management treatments (with and without CRI) were tested in RCBD with 3 replications. Treatments were T1=HYG (0-80-16- 44-12-2-0), T2=MYG (0-56-12-32-8-1.5-0), T3=IPNS (5000-65-13-32-9-2-0), T4=STB (0-68-15-37-11-2-0), T5=FP (0-39-7-12-0-0-0), T6=CON (0-0-0-0-0-0- 0), T7=HYG+CRI(Crop residue incorporation), T8=MYG+CRI, T9=IPNS+CRI, T10=STB+CRI, T11=FP+CRI, T12=CON+CRI kg ha-1 CDNPKSZnB for T. Aman rice. On an average, maximum grain yield of T. Aman rice was obtained from STB+CRI (5.24 t ha-1) followed by IPNS+CRI (5.13 t ha-1), STB (5.12 t ha-1), IPNS (5.03 t ha-1), HYG+CRI (4.50t ha-1) and HYG (4.41 t ha-1). Numerically but not statistically higher yield and yield contributing parameters were noticed in CRI plots than without CRI. Except N and K remaining nutrient balance like P S Zn and B were found positive in case of HYG, MYG, IPNS and STB along with or without CRI nutrient managements while FP and CON (Control) showed negative balance. The maximum BCR was observed in STB (3.25) followed by STB+CRI (3.14) and IPNS (2.98) and similar trend was observed in MBCR. Bangladesh J. Agril. Res. 40(1): 17-34, March 2015